2019
DOI: 10.1038/s41598-019-47918-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between cardiorespiratory fitness/muscular strength and 18F-fluorodeoxyglucose uptake in brown adipose tissue after exposure to cold in young, sedentary adults

Abstract: Humans have metabolically active brown adipose tissue (BAT). However, what is the relation between exercise or physical activity with this tissue remains controversial. Therefore, the main aim of the present study is to examine whether cardiorespiratory fitness and muscular strength are associated with brown adipose tissue (BAT) volume and activity after exposure to cold in young, sedentary adults. Cardiorespiratory fitness was determined in 119 young, healthy, sedentary adults (68% women, age 21.9 ± 2.1 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 46 publications
1
12
0
1
Order By: Relevance
“…The lack of evidence of BAT volume, 18 F-FDG uptake or mean radiodensity modification after exercise training is in line with the results of cross-sectional studies that show no association of BAT-related outcomes with objectively measured free-living physical activity 51 or muscular or cardiorespiratory fitness 52 . Case-control studies have revealed, however, that endurance-trained athletes show lower BAT volumes and 18 F-FDG uptakes than their sedentary counterparts 53 , 54 .…”
Section: Resultssupporting
confidence: 75%
“…The lack of evidence of BAT volume, 18 F-FDG uptake or mean radiodensity modification after exercise training is in line with the results of cross-sectional studies that show no association of BAT-related outcomes with objectively measured free-living physical activity 51 or muscular or cardiorespiratory fitness 52 . Case-control studies have revealed, however, that endurance-trained athletes show lower BAT volumes and 18 F-FDG uptakes than their sedentary counterparts 53 , 54 .…”
Section: Resultssupporting
confidence: 75%
“…In this study, participants, especially men, performing VPA, showed high BAT-d in the supraclavicular region. Information is sparse from human studies investigating the relationship between exercise and BAT; previous studies have focused on aerobic exercise [19,50], vigorous-intensity exercise [25], and muscle strength [64]. This study was the first to observe a relationship between VPA and BAT-d.…”
Section: Discussionmentioning
confidence: 78%
“…On the other hand, two weeks of high intensity interval training and moderate training interventions did not alter 18 F-FDG uptake [25]. A cross-sectional report on the relationship between muscle strength and BAT activity showed a positive correlation between grip strength and BAT activity [64]. The concentration of blood myokine, a marker for promoting WAT browning, has been reported to be higher in an 8-week resistance training group than in control and endurance training groups [75,76].…”
Section: Discussionmentioning
confidence: 98%
“…Thus, exercise has been proven to provide a beneficial effect in animals (Rossi et al 2011) and humans (Martinez-Tellez et al 2019). Exercise treatments for anxiety or depression have been considered a helpful intervention (Wegner et al 2014).…”
Section: Introductionmentioning
confidence: 99%